J/ψ-N center of mass energy dependence of nuclear absorption effect on J/ψ production - 王宏民 侯召宇 刘家福 孙献静 (Chinese physics C, 2010)
In this paper, the J/ψ nuclear absorption effect is studied at RHIC and LHC energies with the EKS98 shadowing parameterizations. By assuming that the J/ψ absorption cross section, σ abs , increases with the charmonium-nucleon （J/ψ-N） center of mass energy, s J/ψN , it is found that σ abs should depend on x F （or y） at a certain center of mass energy per nucleon pair,s , especially at LHC energies. The theoretical results with the x F （or y）-dependence of the absorption effect are in good agreement with the experiment data from PHENIX in d-Au collisions and the predicted results will be examined by the forthcoming experimental data from LHC in d-Pb collisions. Finally, we also present baseline calculations of cold nuclear matter effects on J/ψ production in nucleus-nucleus （A-A） collisions and find that the x F （or y）-dependence of absorption effect is very small at both RHIC and LHC energies in A-A collisions.